First assessment of the performance of an implantable continuous glucose monitoring system through 180 days in a primarily adolescent population with type 1 diabetes - Aronson, Ronnie; Abitbol, Alexander; Tweden, Katherine S. (Diabetes, obesity & metabolism, 2019)
Aim To investigate the performance of the Eversense XL implantable continuous glucose monitoring (CGM) system through 180 days in a primarily adolescent population with type 1 diabetes (T1D). Materials and methods This prospective, single‐centre, single‐arm, 180‐day study evaluated the effectiveness and safety of the implantable CGM system in Canadian adolescent and adult subjects with T1D. Accuracy measures included mean absolute relative difference (MARD), 15/15% agreement between CGM glucose and blood glucose measured by Yellow Springs Instruments and surveillance error grid analysis. Adolescent subjects received one sensor in the upper arm and adult subjects received one sensor in each upper arm. In‐clinic CGM system accuracy studies were performed every 30 days. The safety assessment included the incidence of adverse events related to either device or the insertion/removal procedure through 180 days. Results Thirty‐six subjects (30 adolescent/6 adult, 13 female/23 male, mean age 17 ± 9.2 years, mean body mass index 22 ± 4 kg/m2) received the CGM system. Overall MARD was 9.4% (95% CI: 8.6%‐10.5%). CGM system agreement at 15/15% (N = 7163) through 60, 120 and 180 days was 82.9% (95% CI: 78.4%‐86.1%), 83.6% (95% CI: 80.4%‐85.7%) and 83.4% (95% CI: 79.7%‐85.5%), respectively. Surveillance error grid analysis showed 98.4% of paired values in clinically acceptable error zones A and B. No insertion/removal or device‐related serious adverse events were reported. Conclusion The Eversense XL CGM system is safe and accurate through 180 days in a primarily adolescent population of subjects with T1D.